Efektivitas Manajemen Sekolah untuk Siswa Berkebutuhan Khusus di SMPN 5 Padang - Bestliyanti; Novriyanti, Ernie; Husna, Dinda Rahmatul; Pertiwi, Dwi Citra (Arus Jurnal Pendidikan, 2024)
This research aims to determine the effectiveness of school management in providing inclusive education at SMPN 5 Padang. The research method used was descriptive qualitative with the research subjects being school principals, inclusive teachers and students with special needs (ABK). Inclusive education, as a new concept in Indonesia, aims to ensure the participation of all students in education. However, challenges in changing school management to support inclusion still exist, especially in terms of management that is different from regular schools. The expected results provide a clear picture of the condition of inclusive schools and the importance of effective management in ensuring the success of inclusive education for all students. The research results show that the management of the inclusive education program at SMPN 5 Padang is still not optimal. This is caused by several factors, namely: Lack of human resources and facilities. Schools still lack inclusive teachers and other teaching staff who are competent in handling ABK students. Apart from that, school facilities and infrastructure are also inadequate to support the implementation of inclusive education programs. Ignorance about the aims and benefits of inclusive education. There are still many teachers and school staff who do not fully understand the goals and benefits of inclusive education. This causes them to be less enthusiastic about supporting inclusive education programs.